2021
DOI: 10.3389/fimmu.2021.651056
|View full text |Cite
|
Sign up to set email alerts
|

Immune Infiltration Subtypes Characterization and Identification of Prognosis-Related lncRNAs in Adenocarcinoma of the Esophagogastric Junction

Abstract: The incidence of adenocarcinoma of the esophagogastric junction (AEG) has markedly increased worldwide. However, the precise etiology of AEG is still unclear, and the therapeutic options thus remain limited. Growing evidence has implicated long non-coding RNAs (lncRNAs) in cancer immunomodulation. This study aimed to examine the tumor immune infiltration status and assess the prognostic value of immune-related lncRNAs in AEG. Using the ESTIMATE method and single-sample GSEA, we first evaluated the infiltration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Signaling pathways related to the IL(R)-based signature were analyzed through Gene Set Enrichment Analysis (GSEA). GSEA is commonly used to evaluate the distribution trend of genes in a predefined gene set, which has been widely reported to investigate the biological process difference between subtypes ( 20 , 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Signaling pathways related to the IL(R)-based signature were analyzed through Gene Set Enrichment Analysis (GSEA). GSEA is commonly used to evaluate the distribution trend of genes in a predefined gene set, which has been widely reported to investigate the biological process difference between subtypes ( 20 , 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…The expression profile data of breast cancer patients (n = 998) with complete clinical information were downloaded from TCGA database. The patients were divided into PRMT1 high-and low-expression groups according to the optimal cutoff value calculated using the "survminer" package (https://CRAN.R-project.org/package=survminer, accessed on 11 July 2021) [22,23]. The Kaplan-Meier method was used to assess the efficiency of disease-specific survival (DSS) in high-and low-expression patients.…”
Section: Disease Specific Survival Analysismentioning
confidence: 99%
“…The clusters showed a low correlation. When K = 2, the CDF curve is flat, revealing the correct K ( Wilkerson and Hayes, 2010 ; Senbabaoglu et al, 2014 ; Hu et al, 2021 ). The maximum Calinski-Harabasz (CH) index indicated that K = 2 was the optimal number of clusters ( Supplementary Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%